Oxidative Study of Benzaldehyde by Isoqauinolinium Bromo Chromate - Dwivedi, Arun Kumar; Sharma, K. N.; Dwivedi, Arvind Prasad (JOURNAL OF ADVANCES IN CHEMISTRY, 2019)
The kinetics analysis of the oxidative reaction between benzaldehyde and oxidant is quinolinium Bromo chromate was reported in aqueous 40% acetic acid medium at 313 K. The rate of reaction varies first-power of [IQBC] and [H2SO4], whereas fractional-order kinetics was observed for benzaldehyde. The rate constant gradually increases with decrease in dielectric constant of the medium. The neutral salt does not alter the rate. The metal cations (Cu++) slightly accelerate the rate of oxidation when added to reaction mixture. The study rules out the participation of keto form of substrate in complex formation. Benzoic acid was identified as the end-product in stoichiometrically 1:1 based mechanism. The rate law was derived in accordance with the kinetic results.